2020
DOI: 10.1101/2020.04.30.20083907
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 infection of the placenta

Abstract: Background. The effects of Covid-19 in pregnancy remain relatively unknown. We present a case of second trimester pregnancy with symptomatic Covid-19 complicated by severe preeclampsia and placental abruption.Methods. We analyzed placenta for the presence of SARS-CoV-2 through molecular and immunohistochemical assays and by and electron microscopy, and we measured the maternal antibody response in blood to this infection.Results. SARS-CoV-2 localized predominantly to syncytiotrophoblast cells at the maternal-f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
278
5
26

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(331 citation statements)
references
References 22 publications
22
278
5
26
Order By: Relevance
“…Thus, we finally used single-cell analysis of the syncytiotrophoblast, villous cytotrophoblast, and extravillous trophoblasts -the fetal component of the placenta -that confirmed the low-levels of expression of the canonical entry receptor ACE2 and TMPRSS2 genes (21,22). Conversely, we found that these cells express high-levels of DPP4 and CTSL, two potential mediators of SARS-Cov-2 host cell entry (27,30) that may contribute to the SARS-CoV-2 infection (17,25,26). It is essential to highlight that our scRNA-Seq analysis showed that the non-canonical DPP4 and CTSL entry genes (27,30) are highly co-expressed in syncytiotrophoblast, villous cytotrophoblast, and extravillous trophoblasts cells.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Thus, we finally used single-cell analysis of the syncytiotrophoblast, villous cytotrophoblast, and extravillous trophoblasts -the fetal component of the placenta -that confirmed the low-levels of expression of the canonical entry receptor ACE2 and TMPRSS2 genes (21,22). Conversely, we found that these cells express high-levels of DPP4 and CTSL, two potential mediators of SARS-Cov-2 host cell entry (27,30) that may contribute to the SARS-CoV-2 infection (17,25,26). It is essential to highlight that our scRNA-Seq analysis showed that the non-canonical DPP4 and CTSL entry genes (27,30) are highly co-expressed in syncytiotrophoblast, villous cytotrophoblast, and extravillous trophoblasts cells.…”
Section: Discussionsupporting
confidence: 74%
“…Recent literature has shown placenta cells infected with SARS-CoV-2 in pregnant women diagnosed with moderate to severe COVID-19 (17,25) with findings supporting the possibility of vertical transmission of SARS-CoV-2 (17,26). However, few placenta cells express ACE2 and TMPRSS2 (21,22) required for virus entry, raising the question about whether potential non-canonical molecular mechanisms may be involved in the biological cycle of the virus in these cells.…”
Section: Discussionmentioning
confidence: 91%
“…However, a recent report of 244 consecutive COVID-19 positive children from Wuhan did not find any difference in fecal nucleic acid RT-PCR between children with or without GI symptoms, suggesting that RT-PCR detection of the virus was not due to gut infection but coming instead from the respiratory tract from swallowed sputum 8 . Defining the role of the GI tract in SARS-CoV-2 infection may also help understand the risks of vertical transmission during gestation since amniotic fluid is swallowed by the fetus during gestation and viral contamination has been isolated from the placenta of an affected woman 9 . While samples from affected mothers have so far failed to prove that amniotic fluid, cord blood, and breast milk contain SARS-CoV-2 10 , very limited data are available at this stage for pregnant women with COVID-19, and even fewer data are available on intrauterine vertical transmission 11 .…”
Section: Introductionmentioning
confidence: 99%
“…This literature review comprises 45 COVID-19 positive pregnant women whose placentas and neonates were also analysed by RT-PCR for the presence of SARS-CoV-2. We report no maternal mortality [9][10][11][12][13][14][15][16][17][18][19].…”
Section: Maternal Outcomementioning
confidence: 99%
“…One woman opted for termination of pregnancy due to symptomatic SARS-CoV-2 complicated by severe preeclampsia in the second trimester [15]. Another woman with symptomatic SARS-CoV-2 presented in the second trimester with a miscarriage [17].…”
Section: Maternal Outcomementioning
confidence: 99%